Surgical management of focal chondral defects of the knee: a Bayesian network meta-analysis - Filippo Migliorini; Jörg Eschweiler; Hanno Schenker; Alice Baroncini; Markus Tingart; Nicola Maffulli (Journal of Orthopaedic Surgery and Research, 2021)
Abstract Background Focal chondral defects of the knee are common. Several surgical techniques have been proposed for the management of chondral defects: microfractures (MFX), osteochondral autograft transplantation (OAT), autologous matrix-induced chondrogenesis (AMIC) and autologous chondrocyte implantation (ACI)—first generation (pACI), second generation (cACI) and third generation (mACI). A Bayesian network meta-analysis was conducted to compare these surgical strategies for chondral defects in knee at midterm follow-up. Methods This Bayesian network meta-analysis was conducted according to the PRISMA extension statement for reporting of systematic reviews incorporating network meta-analyses of health care interventions. PubMed, Google Scholar, Embase and Scopus databases were accessed in July 2021. All the prospective comparative clinical trials investigating two or more surgical interventions for chondral defects of the knee were accessed. The network meta-analyses were performed through a Bayesian hierarchical random-effects model analysis. The log odds ratio (LOR) effect measures were used for dichotomic variables, while the standardized mean difference (SMD) for the continuous variables. Results Data from 2220 procedures (36 articles) were retrieved. The median follow-up was 36 (24 to 60) months. The ANOVA test found good baseline comparability between symptoms duration, age, sex and body mass index. AMIC resulted in higher Lysholm score (SMD 3.97) and Tegner score (SMD 2.10). AMIC demonstrated the lowest rate of failures (LOR −0.22) and the lowest rate of revisions (LOR 0.89). As expected, MFX reported the lower rate of hypertrophy (LOR −0.17) followed by AMIC (LOR 0.21). No statistically significant inconsistency was found in the comparisons. Conclusion AMIC procedure for focal chondral defects of the knee performed better overall at approximately 3 years’ follow-up.